PENERAPAN METODE EOQ (ECONOMIC ORDER QUANTITY) DALAM PENGENDALIAN BAHAN BAKU - Rahman Soesilo; Nirfison Nirfison (LPPM Universitas Bina Bangsa, 2022)
A company engaged in aluminum metal makes aluminum frame doors and windows as one of its products. For the purposes of the production process of aluminum frame doors and windows, aluminum metal raw materials are needed. Control of raw material stocks in PT. Al so far still needs to improve its efficiency due to the excessive accumulation of raw materials due to the purchase of raw materials that are still not in accordance with the needs of raw materials for production. Such problems interfere in the production process at the enterprise. Therefore, a careful calculation method is needed accompanied by efficiency and is able to reduce the cost of raw material stock to a minimum. In this study, the Economic Order Quantity (EOQ) method was used to be applied to reduce stock costs to a minimum in terms of storage costs and ordering costs. In this study, data on the cost of procurement of raw materials carried out by the company before the implementation of EOQ amounted to Rp. 5,681,128,000 per year, while after using the EOQ method the total cost was Rp. 1,533,187,750 per year, so that the total savings were Obtained was Rp. 4,147,940,250 per year